GAS SENSITIVE FILMS BASED ON Te-SnO2 NANOCOMPOSITE ON FLEXIBLE SUBSTRATE - TSIULYANU, Dumitru; MOCREAC, Olga; AFANASIEV, Andrei; MONAICO, Eduard (Journal of Engineering Science (Chişinău), 2022)
Flexible films based on novel Te-SnO2 nanocomposites were fabricated for detection of toxic gases at room temperature. The Te-SnO2 nanocomposites were obtained via solvohermal recrystallization of pure crystalline tellurium in nitric acid in the presence of tin chloride. The energy-dispersive X-ray spectroscopy (EDX) and XRD analyses have shown that the Te-SnO2 films consists of fluffy structures of tiny agglomerates of the nanodimensional irregular blocks of hexagonal Te and polycrystalline SnO2. Both current / voltage and transient characteristics of the flexible Te-SnO2 films were investigated at room temperature in ambiance comprising different toxic gases. The maximum selectivity was revealed toward NO2, for which in the dynamic range of 0.5 - 5.0 ppm of NO2, the response and recovery times are about 30 s and 150 s respectively. Analysis of the response kinetics meets the Langmuir theory of adsorption. This study revealed a simple route of fabrication of the printable Te-SnO2 nanocomposites that can be used in electronics, inclusive for development of flexible and compostable gas sensors, operating at room temperature.